PELAKSANAAN PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN PESISIR KECAMATAN LIMAPULUH KOTA PEKANBARU TAHUN 2017 - Veny Risvayanti; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In order to improve the quality of housing and settlements, the government launched a city program without slums (KOTAKU) starting in 2016. The No Slum City Program (KOTAKU) is a program implemented nationally in 271 Regencies / Cities in 34 Provinces that become "collaboration platforms". Pesisir is one of the villages that received the KOTAKU program in Pekanbaru City, the purpose of this study is to see how the Implementation of the No Slum City Program (KOTAKU) in the Pesisir Sub-District of Pekanbaru City and what are the factors that inhibit the KOTAKU Program Implementation . This research was conducted in Pesisir Sub-District, Limapuluh Subdistrict, Pekanbaru City. The theoretical concept used in this research is Manullang theory management which has four management function indicators, namely planning, organizing, directing, and controlling. The research method used is qualitative with data collection techniques through interviews, observation and documentation. The selection of research informants used purposive sampling technique. The results of this study indicate that the implementation of the No Slum City Program (KOTAKU) in Pesisir Sub-District of Limapuluh Kota District in 2017 has not been carried out optimally. In the planning stage there were people who agreed and disagreed when eating the road and their home page was used for more environment well. At the stage of organizing a miss communication between the LKM and the KSM. At the implementation stage there were still delays in work assignments in the field, while the factors that hampered the implementation of the No Slum City (KOTAKU) program in Pesisir Village were community participation.Keywords : Implementation, No Slum City Program (KOTAKU)